Examining the relationship between the Russian Orthodox Church and secular authorities in the 19th and 20th centuries - Eršov, Bogdan Anatolʹevič (Information Science Reference, 2022)
Historiography of the problem -- Study sources -- State legal regulation of the Church -- Church as a social and spiritual institution of society -- The role of the Church in the life of nobles and peasants -- Church and secular authority -- White and black clergy -- Spiritual education system -- Family basics of the life of clerics -- Church charities and institutions -- Communities of the Sisters of Mercy and the Orthodox Church -- Folk tradition of Orthodox pilgrimage in the sphere of church and state relations -- Church land tenure and land use -- Missionary activity of the Church -- Orthodox posts in the life of the Russian province.